Post-treatment method for composite additive
By adopting the post-treatment method of composite additives in metal additive manufacturing, using arc cladding technology to form an outer coating and fill the cavity, the problem of physical defects and mechanical properties in additive manufacturing in the prior art is solved, and higher mechanical properties and lower production costs are achieved.
Patent Information
- Application Number
- CN202510011419.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-03
AI Technical Summary
Existing metal additive manufacturing methods have physical defects such as cracks, and are low in cost and efficiency, especially in the case of poor interface bond between the shell material and the inner layer material, the difference in thermal expansion coefficient leads to the failure of mechanical properties.
Using the post-treatment method of composite additives, the metal powder is dispersed in hot melt organic materials, formed paste and dried, the additive with cavity is constructed using three-dimensional printing technology, and the outer coating is formed through arc cladding technology, the cavity is filled with semi-solid slurry, and the thermal expansion coefficient gradient is controlled to avoid cracking.
Improves the mechanical properties of the shell, avoids cracking in high temperature environments, reduces the workload of the three-dimensional printing steps, reduces costs and improves production efficiency.
Smart Images

Figure CN119703058A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semi-solid alloy materials, and in particular to a post-processing method for composite additives. Background Art
[0002] Additive manufacturing technology, also known as 3D printing technology, can be used for personalized and miniaturized parts manufacturing, which can reduce material consumption and improve production efficiency. Additive printing technology has achieved great success in the application of plastic additives, but its application in metal additives faces great challenges. Metal additive manufacturing methods include selective arc cladding, electron beam melting molding, laser powder deposition, etc. However, metal additives manufactured by these methods have many physical defects such as cracks, and have great disadvantages in cost and efficiency.
[0003] GB2519134A discloses a method for manufacturing a three-dimensional object, including using a 3D printing method to form an object with a cavity, and then filling the cavity with a filler to increase the rigidity of the object to form a three-dimensional object. The text uses a thermosetting material as the material of the shell, and a solid material or a thermosetting resin with relatively high strength as the filling material, thereby improving the rigidity of the three-dimensional object. Applying the above technology to the field of metal additive manufacturing is conducive to reducing costs and improving efficiency, but the shell material and the inner layer material of the above method are divided into secondary molding, and it is difficult to form a better interface bonding between the inner and outer layer materials, and it is difficult to process the inner surface of the shell material to improve the interface bonding effect, especially when the thermal expansion coefficient of the shell material and the inner layer material is large, after heat treatment, it is easy to cause the interface bonding effect to be further reduced, resulting in the mechanical properties of the produced three-dimensional object failing to meet the requirements.
[0004] Therefore, it is necessary to provide a post-processing method for composite additives. Summary of the invention
[0005] In order to solve the problem of poor composite effect of composite additives, it is necessary to provide a post-processing method for composite additives.
[0006] A post-processing method for composite additives comprises the following steps: Dispersing metal powder A in a hot-melt organic material to obtain a paste; Drying the paste to obtain powder; Using the powder as a raw material and adopting a three-dimensional printing method to construct an additive material having a cavity, wherein the volume of the cavity accounts for 70-90% of the volume of the additive material; Degreasing the additive material, and then treating the additive material by arc cladding technology to form an outer coating, wherein the material of the coating is C; The semi-solid slurry B is filled into the cavity, and after the additive material is cooled, the composite additive material is obtained, and the thermal expansion coefficient of A is greater than that of B and C.
[0007] In this scheme, a shell with a cavity is formed by additive manufacturing technology, and the outer surface of the additive is post-processed by arc cladding technology to form a coating. Under the action of arc cladding, the hot-melt organic material remaining in the shell is further decomposed to produce pores, and the material C of the coating forms a melt under the action of arc cladding to fill the pores to avoid shrinkage of the shell after cooling. At the same time, under the action of arc cladding, the metal particles A of the shell are fused with the material C to form a shell with higher mechanical strength. Therefore, when the cavity volume accounts for a large proportion, the shell will not be deformed during the pouring process into the cavity. During the pouring process, the liquid phase component in the semi-solid metal solution B can diffuse into the pores of the shell, further improving the interface bonding effect between the shell and the inner layer material, and the inner layer material, the composite layer of the inner layer material and the shell, and the composite layer formed by the shell and material C avoid a sudden change in the thermal expansion coefficient, thereby avoiding cracking in subsequent heat treatment or high temperature environment, resulting in a decrease in the mechanical properties of the composite additive.
[0008] Furthermore, the volume of the cavity accounts for 80-90% of the volume of the additive material. The post-processing method of the composite additive material can make the shell material have higher mechanical properties, thereby allowing the cavity to have a higher volume ratio, which can reduce the workload of the three-dimensional printing step, reduce costs and improve production efficiency.
[0009] Furthermore, the solid fraction of the semi-solid slurry B is 50-60%. The semi-solid slurry with the above solid fraction has better fluidity and is not prone to produce many shrinkage cavities after cooling, so that a composite additive with better mechanical properties can be obtained.
[0010] Furthermore, the thermal expansion coefficient of A is 1.05-1.1 times that of B, and the thermal expansion coefficient of C is 0.95-1.05 times that of B. In this way, the three layers of materials, namely, the inner layer material (B), the composite layer of the inner layer material and the outer shell (A+B), and the composite layer (A+C) formed by the outer shell and the material C, can form a gradient increase in the thermal expansion coefficient, further avoiding cracking during the heat treatment process.
[0011] Furthermore, the thermal expansion coefficient of A is 22×10 -6 / ℃-23.6×10 -6 / ℃, the thermal expansion coefficient of B is 20×10 -6 / ℃-22.5×10 -6 / ℃, the thermal expansion coefficient of C is 19×10 -6 / ℃-23.6×10 -6 / °C. The thermal expansion coefficient in this application refers to the data of the material at 20-100°C.
[0012] Furthermore, the A material is 6013, the B material is A356.2, and the C material is 4032.
[0013] Furthermore, the parameters of the arc cladding technology are: current 80-120A, voltage 10-12V, argon atmosphere Furthermore, an ultrasonic effect is applied to the additive material during post-processing to promote diffusion of the material C in the pores of the shell, thereby forming a better bonding effect.
[0014] Furthermore, the parameters of the ultrasonic action are 1000-2000W, 10-35kHz.
[0015] Furthermore, the catalyst for the degreasing treatment is HNO3. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a graph showing the tensile stress test results of Example 1 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0017] For ease of understanding of the application, the application will be described more fully below. The application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.
[0018] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0020] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0021] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0022] The percentage contents involved in this application, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.
[0023] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.
[0024] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.
[0025] The "particles" mentioned in this application, or materials with a defined particle size distribution, are not necessarily spherical in shape, but may be irregular, primary particles or secondary particles. The particle size of irregular particles is the average of their maximum diameter and minimum diameter.
[0026] The following A356.2 metal powder composition (thermal expansion coefficient 21.4×10 -6 / ℃) is: by weight: silicon 6.5%, magnesium 0.4%, titanium 0.1%, iron 0.08%, copper 0.05%, manganese 0.02%, zinc 0.04%, and the balance is aluminum.
[0027] The following composition of 6061 aluminum alloy (thermal expansion coefficient 23.4×10 -6 / ℃) is: by weight: 1% magnesium, 0.6% silicon, 0.25% copper, 0.15% titanium, 0.25% zinc, and the balance is aluminum.
[0028] The following composition of 4032 aluminum alloy (thermal expansion coefficient 19.4×10 -6 / ℃) is: by weight: 12.5% silicon, 1% copper, 1.3% magnesium, 0.2% zinc, 0.05% chromium, 1% nickel, and the balance is aluminum.
[0029] The following composition of 6101 aluminum alloy (thermal expansion coefficient is 23×10 -6 / ℃) is: silicon 0.5%, iron 0.3%, copper 0.1%, magnesium 0.5%, zinc 0.08% and the balance aluminum.
[0030] Embodiment 1: This embodiment provides a post-processing method for composite additives, comprising the following steps: The 6013 aluminum alloy particles were dried and mixed with PLA for 2 hours to obtain a paste, in which the weight proportion of metal particles was 85% and the average particle size of the metal powder was 20 μm; The paste is cooled and the dried cake is crushed to obtain powder, which is metal particles with PLA covered on the surface; Using powder as raw material, a 3D printer is used to print a part with a cavity of a preset shape, where the cavity volume accounts for 90% of the part volume; The parts with cavities were placed in a degreasing furnace for degreasing, catalytic gas HNO3 was introduced and heated at 110°C for 3h to complete the degreasing; The surface of the parts is post-processed by arc cladding technology to form an outer coating with a coating thickness of 1 mm and a coating material of A356.2; A semi-solid A356.2 aluminum alloy melt with a solid phase fraction of 50% is prepared, and the melt is injected into the cavity of the post-processed part, and the composite additive is obtained by cooling.
[0031] Embodiment 2: This embodiment provides a post-processing method for composite additives, comprising the following steps: The 6013 aluminum alloy particles were dried and mixed with PLA for 2 hours to obtain a paste, in which the weight proportion of metal particles was 85% and the average particle size of the metal powder was 20 μm; The paste is cooled and the dried cake is crushed to obtain powder, which is metal particles with PLA covered on the surface; Using powder as raw material, a 3D printer is used to print a part with a cavity of a preset shape, where the cavity volume accounts for 70% of the part volume; The parts with cavities were placed in a degreasing furnace for degreasing, catalytic gas HNO3 was introduced and heated at 110°C for 3h to complete the degreasing; The surface of the parts is post-processed by arc cladding technology to form an outer coating with a coating thickness of 1 mm and a coating material of A356.2; A semi-solid A356.2 aluminum alloy melt with a solid phase fraction of 60% is prepared, and the melt is injected into the cavity of the post-processed part, and the composite additive is obtained by cooling.
[0032] Embodiment 3: This embodiment provides a post-processing method for composite additives, comprising the following steps: The 6013 aluminum alloy particles were dried and mixed with PLA for 2 hours to obtain a paste, in which the weight proportion of metal particles was 75% and the average particle size of the metal powder was 20 μm; The paste is cooled and the dried cake is crushed to obtain powder, which is metal particles with PLA covered on the surface; Using powder as raw material, a 3D printer is used to print a part with a cavity of a preset shape, where the cavity volume accounts for 80% of the part volume; The parts with cavities were placed in a degreasing furnace for degreasing, catalytic gas HNO3 was introduced and heated at 110°C for 3h to complete the degreasing; The surface of the parts is post-processed by arc cladding technology to form an outer coating with a coating thickness of 1 mm and a coating material of A356.2; A semi-solid A356.2 aluminum alloy melt with a solid phase fraction of 50% is prepared, and the melt is injected into the cavity of the post-processed part, and the composite additive is obtained by cooling.
[0033] Embodiment 4: This embodiment provides a post-processing method for composite additives, comprising the following steps: The 6013 aluminum alloy particles were dried and mixed with PLA for 2 hours to obtain a paste, in which the weight proportion of metal particles was 85% and the average particle size of the metal powder was 20 μm; The paste is cooled and the dried cake is crushed to obtain powder, which is metal particles with PLA covered on the surface; Using powder as raw material, a 3D printer is used to print a part with a cavity of a preset shape, where the cavity volume accounts for 90% of the part volume; The parts with cavities were placed in a degreasing furnace for degreasing, catalytic gas HNO3 was introduced and heated at 110°C for 3h to complete the degreasing; The surface of the parts is post-processed by arc cladding technology to form an outer coating, the coating thickness is 1mm, and the coating material is 4032; A semi-solid A356.2 aluminum alloy melt with a solid phase fraction of 50% is prepared, and the melt is injected into the cavity of the post-processed part, and the composite additive is obtained by cooling.
[0034] Embodiment 5: This embodiment provides a post-processing method for composite additives, comprising the following steps: The 6013 aluminum alloy particles were dried and mixed with PLA for 2 hours to obtain a paste, in which the weight proportion of metal particles was 85% and the average particle size of the metal powder was 20 μm; The paste is cooled and the dried cake is crushed to obtain powder, which is metal particles with PLA covered on the surface; Using powder as raw material, a 3D printer is used to print a part with a cavity of a preset shape, where the cavity volume accounts for 90% of the part volume; The parts with cavities were placed in a degreasing furnace for degreasing, catalytic gas HNO3 was introduced and heated at 110°C for 3h to complete the degreasing; The surface of the parts is post-processed by arc cladding technology to form an outer coating with a coating thickness of 1 mm and a coating material of A356.2. Ultrasonic action is applied to the parts during post-processing with the parameters of 2000 W and 10 kHz. A semi-solid A356.2 aluminum alloy melt with a solid phase fraction of 50% is prepared, and the melt is injected into the cavity of the post-processed part, and the composite additive is obtained by cooling.
[0035] Embodiment 6: This embodiment provides a post-processing method for composite additives, comprising the following steps: The 6013 aluminum alloy particles were dried and mixed with PLA for 2 hours to obtain a paste, in which the weight proportion of metal particles was 85% and the average particle size of the metal powder was 20 μm; The paste is cooled and the dried cake is crushed to obtain powder, which is metal particles with PLA covered on the surface; Using powder as raw material, a 3D printer is used to print a part with a cavity of a preset shape, where the cavity volume accounts for 90% of the part volume; The parts with cavities were placed in a degreasing furnace for degreasing, catalytic gas HNO3 was introduced and heated at 110°C for 3h to complete the degreasing; The surface of the parts is post-processed by arc cladding technology to form an outer coating with a coating thickness of 2 mm and a coating material of A356.2. Ultrasonic action is applied to the parts during post-processing with the parameters of 1000 W and 35 kHz. A semi-solid 6101 aluminum alloy melt with a solid phase fraction of 50% is prepared, and the melt is injected into the cavity of the post-processed part, and the composite additive is obtained by cooling.
[0036] Comparative Example 1: This embodiment provides a post-processing method for composite additives, comprising the following steps: The 6013 aluminum alloy particles were dried and mixed with PLA for 2 hours to obtain a paste, in which the weight proportion of metal particles was 85% and the average particle size of the metal powder was 20 μm; The paste is cooled and the dried cake is crushed to obtain powder, which is metal particles with PLA covered on the surface; Using powder as raw material, a 3D printer is used to print a part with a cavity of a preset shape, where the cavity volume accounts for 90% of the part volume; The parts with cavities were placed in a degreasing furnace for degreasing, catalytic gas HNO3 was introduced and heated at 110°C for 3h to complete the degreasing; A semi-solid A356.2 aluminum alloy melt with a solid phase fraction of 50% was prepared and injected into the cavity of the part. During the pouring process, the additive material was significantly deformed.
[0037] Comparative Example 2: This embodiment provides a post-processing method for composite additives, comprising the following steps: The 6013 aluminum alloy particles were dried and mixed with PLA for 2 hours to obtain a paste, in which the weight proportion of metal particles was 85% and the average particle size of the metal powder was 20 μm; The paste is cooled and the dried cake is crushed to obtain powder, which is metal particles with PLA covered on the surface; Using powder as raw material, a 3D printer is used to print a part with a cavity of a preset shape, where the cavity volume accounts for 90% of the part volume; The parts with cavities were placed in a degreasing furnace for degreasing, catalytic gas HNO3 was introduced and heated at 110°C for 3h to complete the degreasing; The surface of the parts is post-processed by arc cladding technology to form an outer coating with a coating thickness of 1 mm and a coating material of 6013; A semi-solid A356.2 aluminum alloy melt with a solid phase fraction of 50% is prepared, and the melt is injected into the cavity of the post-processed part, and the composite additive is obtained by cooling.
[0038] Comparative Example 3: This embodiment provides a post-processing method for composite additives, comprising the following steps: The 6013 aluminum alloy particles were dried and mixed with PLA for 2 hours to obtain a paste, in which the weight proportion of metal particles was 85% and the average particle size of the metal powder was 20 μm; The paste is cooled and the dried cake is crushed to obtain powder, which is metal particles with PLA covered on the surface; Using powder as raw material, a 3D printer is used to print a part with a cavity of a preset shape, where the cavity volume accounts for 90% of the part volume; The parts with cavities were placed in a degreasing furnace for degreasing, catalytic gas HNO3 was introduced and heated at 110°C for 3h to complete the degreasing; The surface of the parts is post-processed by arc cladding technology to form an outer coating with a coating thickness of 1 mm and a coating material of A356.2; A semi-solid A356.2 aluminum alloy melt with a solid phase fraction of 20% is prepared, and the melt is injected into the cavity of the post-processed part, and the composite additive is obtained by cooling.
[0039] Mechanical properties test The mechanical properties of the additives of various embodiments and comparative examples at room temperature were tested with reference to standard GB / T 228.1-2010 “Tensile test of metallic materials Part 1: Room temperature test method”.
[0040] Table 1 Yield strength and tensile strength of the additives of various embodiments and comparative examples.
[0041]
[0042] According to the data in Table 1, the mechanical properties of Examples 1-6 are significantly higher than those of Comparative Examples 2-3, and the shell of Comparative Example 1 is deformed during the casting process. This is because the present solution forms a shell with a cavity by using additive manufacturing technology, and the outer surface of the additive is post-processed by arc cladding technology to form a coating. Under the action of arc cladding, the hot-melt organic material remaining in the shell is further decomposed to produce pores, and the material C of the coating forms a melt under the action of arc cladding to fill the pores to avoid shrinkage of the shell after cooling. At the same time, the metal particles of the shell are deformed under the action of arc cladding. A fuses with material C to form a shell with higher mechanical strength. Therefore, when the volume of the cavity accounts for a large proportion, the shell will not deform during the pouring process into the cavity. During the pouring process, the liquid phase components in the semi-solid metal solution B can diffuse into the pores of the shell, further improving the interface bonding effect between the shell and the inner layer material, and the inner layer material, the composite layer of the inner layer material and the shell, and the composite layer formed by the shell and material C avoid sudden changes in the thermal expansion coefficient, thereby avoiding cracking during subsequent heat treatment or high temperature environment, resulting in a decrease in the mechanical properties of the composite additive. Comparative Example 1 did not undergo post-processing. After degreasing, its shell had low mechanical strength, and the cavity accounted for a large proportion. It was easy to deform during the pouring process and could not meet the requirements of precision manufacturing. Comparative Example 2 used materials A and C with the same thermal expansion coefficient. The thermal expansion coefficients between the inner and outer layer materials differed greatly, and they were prone to fracture after heat treatment, resulting in reduced mechanical properties. Comparative Example 3 uses semi-solid slurry B with a lower solid phase fraction. During the casting process, the liquid phase components are easy to seep out from the pores of the shell, and shrinkage cavities are easy to form during the cooling process, resulting in a decrease in its mechanical properties.
[0043] Example 4 uses 4032 material with a large difference in thermal expansion coefficient from A and B, which can better balance the difference in thermal expansion coefficient between materials AB. The three layers of materials, the inner layer material (B), the composite layer of the inner layer material and the outer shell (A+B), and the composite layer formed by the outer shell and material C (A+C), can form a gradient increase in thermal expansion coefficient, further avoiding cracking during the heat treatment process. Example 5 uses ultrasonic treatment to promote the diffusion of material C in the pores of A and form a better bond.
[0044] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0045] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A post-processing method for composite additives, characterized in that: The following steps are involved: Dispersing metal powder A in a hot-melt organic material to obtain a paste; Drying the paste to obtain powder; Using the powder as a raw material and adopting a three-dimensional printing method to construct an additive material having a cavity, wherein the volume of the cavity accounts for 70-90% of the volume of the additive material; Degreasing the additive material, and then post-treating the additive material by arc cladding technology to form an outer coating, wherein the material of the coating is C; The semi-solid slurry B is filled into the cavity, and after the additive material is cooled, the composite additive material is obtained, and the thermal expansion coefficient of A is greater than that of B and C.
2. The preparation method according to claim 1, characterized in that: The volume of the cavity accounts for 80-90% of the volume of the additive.
3. The preparation method according to claim 1, characterized in that: The solid fraction of the semi-solid slurry B is 50-60%.
4. The preparation method according to claim 1, characterized in that: The thermal expansion coefficient of A is 1.05-1.1 times that of B, and the thermal expansion coefficient of C is 0.95-1.05 times that of B.
5. The preparation method according to claim 1, characterized in that: The thermal expansion coefficient of A is 22×10 -6 / ℃-23.4×10 -6 / ℃, the thermal expansion coefficient of B is 20×10 -6 / ℃-22.5×10 -6 / ℃, the thermal expansion coefficient of C is 19×10 -6 / ℃-23.4×10 -6 / ℃.
6. The preparation method according to claim 1, characterized in that: The A material is 6013, the B material is A356.2, and the C material is 4032.
7. The preparation method according to claim 1, characterized in that: The parameters of the arc cladding technology are: current 80-120A, voltage 10-12V, and argon atmosphere.
8. The preparation method according to claim 1, characterized in that: Ultrasonic action is applied to the added material during post-processing.
9. The preparation method according to claim 8, characterized in that: The parameters of the ultrasonic action are 1000-2000W, 10-35kHz.
10. The preparation method according to claim 1, characterized in that: The catalyst for the degreasing treatment is HNO3.
Citation Information
Patent Citations
Manufactured metal objects with hollow channels and method for fabrication thereof
CA3048456A1
Method for producing molded article by sintering
CN116438150A
Powder particle enhanced metamaterial and manufacturing method thereof
CN118357462A
Process for the production of a composition consisting of reinforcing threads and a resin matrix
DE2351360A1
Method for Forming Complex Hollow Models from Low Modulus Material
US20210060869A1